Ageing is correlated to salt taste threshold among elderly - Farapti, Farapti; Fadilla, Chusnul; Hasanatuludhhiyah, Nurina; Rezeki, Purwo Sri; Miftahussurur, Muhammad (Universiti Kebangsaan Malaysia, 2022)
Ageing may coincide with an increasing taste loss that can affect intake and consequently produce negative health impact. This study was conducted to analyze salt taste threshold (STT) in older people and investigate the correlation between ageing and STT among elderly in the nursing home. Recognition threshold of salty was measured using sodium chloride in liquid with the 3 ascending concentration series method. This study showed 18.5% of subjects had poor salt sensitivity. Overall, there was correlation between ageing and STT, it means the older an elderly was, the higher the STT would be (r=0.401, p=0.003). Further analysis based on gender showed the significant increase in STT was only found in male subjects. The increasing age among elderly was associated significantly with declining salt taste sensitivity. Understanding the decline of salt taste sensitivity among ageing population in the nursing home is useful for formulating food recipes for especially hypertensive elderly.